DIFFERENCE TIME APPLICATION OF AUXIN (NAA) ON GROWTH AND YIELD OF BLACK RICE (Oryza sativa var. Cempo Ireng) WITH SRI METHOD (System of Rice Intensification) - SOPYANA TSAURI (nim : 11414017), FIKRI
Black rice (Oryza sativa var. Cempo Ireng) is a local cultivar that produces black rice as a highly nutritious functional food. The age is classified as moderate (120-150 DAT) with typical growth phases including vegetative phase, generative phase, and panicle filling phase. The productivity of this plant also tends to be low compared to white rice, therefore it is necessary to increase through intensification. Auxin application (NAA) is a technique that can be used to stimulate the growth and yield of rice plants. Typical growth phases in rice plants indicate a different physiological process in each phase so that demands for different auxin requirements are needed, therefore the timing of suitable applications can determine the influence of auxins on the growth and yield of black rice plants. This study aims to determine the effect of auxin application time (NAA) on the growth and yield of black rice and obtain a suitable auxin application time to improve growth and yield of black rice on the SRI method. The study design used Randomized Block Design (RBD) with 4 treatments consisting of without application treatment (A), application of vegetative phase (B), application of generative phase (C), and application of panicle filling phase (D). Each treatment was repeated 7 times. The results of the study showed that the difference of auxin application time did not give a significant effect on the number of leaves, plant height, number of tillers, flowering time, number of panicles per hill, number of filled grains per panicle, dry weight of shoots, dry weight of roots, weight of 1000 grains, plant productivity, and the harvest index of black rice (Oryza sativa var. Cempo Ireng) in the SRI method. Treatment without application tends to show the highest growth response with the number of leaves (184 leaves), plant height (79.00 cm) and number of tillers (46.57 tillers). Treatment application of vegetative phase tends to show the best results with root dry weight (32.10 grams), filled grain per panicle (143.43 grain) and plant productivity (3.74 tons / ha).